ANALISIS PARAMETER INJECTION MOLDING TERHADAP WAKTU SIKLUS DAN CACAT FLASH PRODUK TUTUP BOTOL 180 ML MENGGUNAKAN METODE TAGUCHI - Andika Wahyu Prasanko; Dwi Djumhariyanto; Agus Triono (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
At present plastic becomes inseparable from human life especially in the food and beverage industry. One of the methods used in the manufacturing process of plastic products is injection molding. Injection molding is one of manufacturing technique that consists of a series of cyclical processes and is used to produce thermoplastic materials. The effect of the combination of process parameters impact on the product results such as the quantity and quality of the product, the non-conformity of the parameters causes the production to be not optimal. One method that can be used for optimization is the taguchi method. The taguchi method is a set of special matrices called orthoghonal arrays that are used as reference in the determination combination of parameters and level values. The purpose of this research is to determine the optimal cycle time and net of the product on the process of making 180 ml bottle cap but by minimizing flash defects. The method used in this phase is ANOVA, and the calculation of taguchi method by using minitab 16 software. From the result of the research, the result of optimal condition is combination injection pressure 1320 bar, injection speed 50 mm/s, holding pressure 300 bar, and nozzle temperature 255oC produces a cycle time value of 15.72 seconds and netto 3.56 grams. This result is better than the setting of the company that produces 16.66 seconds cycle time and entered in the net range of 4 ± 0.5 grams resulting in an increase in production of 5.97%. While with combination of injection pressure 1280 bar, injection speed 50 mm / s, holding pressure 300 bar, and nozzle temperature 245oC resulted in fewer number of flash defects compared to company setting that is 12 units from 80 units of sample. Keywords: flash deffect, injection molding, taguchi method, cycle time